Obtaining biogas during fermentation of fat-containing wastes of leather production - Golub, Nataliia; Shynkarchuk, Malvina; Kozlovec, Alexandr (Eastern-European Journal of Enterprise Technologies, 2017)
The possibility of biogas formation from wastes of fat-containing raw material, formed at different stages of the process of leather production was determined. The influence of impurities, which are used in the production process, on the yield of biogas and content of methane in it was shown. Fatty wastes that contain a significant amount of salts, SAS, and antiseptics, have twice as low rate of biogas formation. Existence of soda contributes to the process of methane genesis due to stabilization of pH value. The yield of methane and biogas from pure fat of pigs was lower than that while using wastes, containing impurities of salts. The rational parameters of fat-containing raw material for obtaining maximum yield of biogas and methane in it were determined. It was shown that the concentration of the substrate from wastes of treated skins pigs should not exceed 7.5 % or 13 g/dm3. Obtained laboratory results make it possible to develop the technology of anaerobic fermentation of fat-containing wastes of leather production, containing inorganic and organic impurities. The technology will enable us to solve environmental problems of waste disposal and to obtain the power carrier and a fertilizer.